Effects of Film Formation on the Electrodeposition of Lithium. Issue 21 (29th September 2020) - Yoshii, Kazuki; Kiuchi, Hisao; Taguchi, Noboru; Shikano, Masahiro; Matsubara, Eiichiro; Sakaebe, Hikari
Abstract: Metallic lithium is the most popular anode material used in next‐generation secondary batteries to achieve high energy densities. However, inhomogeneous deposition is a serious issue that must be addressed for large‐scale implementation. Previous studies have highlighted that a surface film formed during the early stages of deposition may have an effect on deposition morphology. Lithium fluoride (LiF) is one of the main components in this surface film, and is thought to play an important role in the subsequent metallic lithium deposition. This study investigated the electrodeposition of lithium using 1.0 mol dm −3 LiPF6 /propylene carbonate (PC) with and without trace amounts of water. The correlation between the morphology of the deposited metallic lithium and surface film formation during galvanostatic deposition was investigated. The morphology of the deposited lithium metal was dependent on the elapsed time after adding water to the electrolyte. X‐ray photoelectron spectroscopy and electrochemical quartz crystal microbalance analyses of the surface film confirmed that the amount of LiF in the film had a large effect on the morphology of the deposited metallic lithium. This study provides a basic understanding of lithium metal deposition and can guide improvements in electrolyte design for battery manufacturing. Abstract : A fine balance : The morphology of electrodeposited lithium is affected by the addition of a trace amount of water to the electrolyte. The effects are also dependent on the amount of water added and the time elapsed after the addition. The film formed during the early stages of galvanostatic deposition is analyzed by X‐ray and electrochemical quartz crystal microbalance measurements, which reveal that the amount of LiF in the film greatly affects the morphology of subsequently deposited metallic lithium.